2003
DOI: 10.1029/2002ja009332
|View full text |Cite
|
Sign up to set email alerts
|

Properties of localized, high latitude, dayside aurora

Abstract: [1] The FUV instrument on the IMAGE spacecraft frequently observes intense ultraviolet (UV) emission from a localized dayside region poleward of the general auroral oval location. One type of these emissions has been described as the signature of direct proton precipitation into the cusp after lobe reconnection during northward interplanetary magnetic field (IMF) and high solar wind dynamic pressure periods . Here we describe a completely different type of high latitude aurora, which does not show any signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 34 publications
9
79
0
Order By: Relevance
“…The absence of polar arcs in case 2 (20 November 2007) may be partly due to the high plasma density density (10-20 cm −3 ) in this ICME case. This is consistent with a previous result indicating that polar arcs under the prevailing southwest IMF conditions are favoured by low solar wind density (Frey et al, 2003). This effect comes in addition to the negative B x component which is unfavourable for lobe reconnection to occur in the Southern Hemisphere.…”
Section: Summary and Discussionsupporting
confidence: 81%
“…The absence of polar arcs in case 2 (20 November 2007) may be partly due to the high plasma density density (10-20 cm −3 ) in this ICME case. This is consistent with a previous result indicating that polar arcs under the prevailing southwest IMF conditions are favoured by low solar wind density (Frey et al, 2003). This effect comes in addition to the negative B x component which is unfavourable for lobe reconnection to occur in the Southern Hemisphere.…”
Section: Summary and Discussionsupporting
confidence: 81%
“…Figure 13 shows IMAGE WIC images (northern hemisphere) from 16:19 UT to 16:49 UT, where this spot is seen clearly detached from the 15 auroral oval in all the ten images (see also the video, uploaded as auxiliary data). Frey et al (2003bFrey et al ( , 2004) explored statistically the characteristics of this high-latitude dayside aurora (HiLDA) and concluded that the major driving process was high-latitude (lobe) reconnection and that it occurred preferentially in the summer hemisphere.…”
Section: This Feature > 75mentioning
confidence: 99%
“…From the direct observations of the electron precipitation flux (reaching 5 keV energy) on 4 December 1999 we infer that similar electron precipitation events, although mostly at lower energies, are present in the case of the type 3 PMAFs. Statistical observations from space indicate that such arcs show a maximum during the sunlit summer months (Frey et al, 2004). The present ground observations show that, given the appropriate interplanetary triggers, intense flow shear arcs are also present in winter.…”
Section: Discussionmentioning
confidence: 68%
“…This interpretation in terms of flow shear arcs (FSAs) is most easily applicable to the strongly distorted dusk-centered convection cells appearing during positive IMF B y conditions. According to Frey et al (2004) such high-latitude dayside arcs (HiLDAs) "shows a maximum in the Northern Hemisphere during sunlit summer months and an almost complete absence in the dark winter." Representative examples of winter PBIs are the 09:20 UT brightening arcs observed in both B y >0 cases reported here (3 December 1997 and4 December 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation